Occurrence of serological reactions for serogroup Sejroe (CTG and Prajtino) in female buffalo in the state of Pernambuco, Brazil - Fernandes de Oliveira, Pollyanne Raysa; Ferreira Soares, Larice Bruna; Borges, Jonas de Melo; Barrosa, Noelle de Castro [UNESP]; Langoni, Helio [UNESP]; Brandespim, Daniel Friguglietti; Pinheiro Junior, Jose Wilton; Mota, Rinaldo Aparecido (Soc Brasileira Microbiologia, 2018)
The objective of this study was to evaluate the occurrence of anti-Leptospira spp. antibodies in female buffalo in the state of Pernambuco. A total of 123 female buffalo blood samples were collected from five properties distributed in the state of Pernambuco. The microscopic agglutination test was used to study anti-Leptospira spp. antibodies. The occurrence of anti-Leptospira spp. antibodies was 28.5% (35/123; CI 20.7-37.3%) and on different properties, the occurrence ranged from 28.6% to 80.0%, with 100% of the properties showing animals with positive results. The serovars of the serogroup Sejroe with a higher incidence were Hard-joprajtino (CTG strain, 49.1%) and Hardjo (Prajtino genotype, 43.2%), followed by serogroup Grippotyphosa with the Grippotyphosa serovar (3.9%), serogroup Pomona with the Pomona serovar (1.9%), and the Icterohaemorrhagiae serovar Copenhageni (1.9%). This was the first record of the occurrence of anti-Lepstospira spp. antibodies in female buffalo in the state of Pernambuco. Control measures are necessary to prevent health and economic losses, given that the agent involved affects animal reproduction, triggering drops in conception rates or even clinical cases of abortion. (C) 2018 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: Leptospirosis; Epidemiology; Bubalusbubalis